Utilization of Internet of Things on Food Supply Chains in Food Industry - Hanhan Maulana; Selvia Lorena Br Ginting; Pramanda Aryan; Muhamad Restu Fadillah; Rubi Nurajmi Kamal (Universitas Komputer Indonesia, 2021)
This study aims to analyze the use of the Internet of Things (IoT) in supporting the management of food supply chains (FSCs) in the food industry. This research used qualitative research methods. The results obtained from this study are increasing the effectiveness and efficiency of the existing food supply chain in the food industry by applying the IoT concept to food supply chain management. These results can be obtained because the IoT concept is supported by various systems and technologies that can be implemented and developed so that IoT can help identify and deal with existing problems more quickly while being able to assist in the decision-making process with information obtained through IoT technology so that it will support development food supply chain management in the food industry. This study was conducted to see how much influence the internet of things (IoT) has on food supply chain management in the food industry.